Iatrogenic injury arising from inappropriate handling of unna boot: experience report (Research, Society and Development, 2022)
Unna boot therapy requires from the nurse an intense commitment related to technical and scientific knowledge, in order to eradicate possible complications. This study aims to report the experience of the Healing Program in the face of care for people with venous ulcers and the iatrogenic consequences resulting from inadequate handling of Unna boot. The methodology applied refers to an experience report, with a descriptive and qualitative approach, developed by a research and extension program of the undergraduate nursing course at the Federal University of São João Del Rei - Campus Centro Oeste, which provides care to people with skin lesions in the University Stomatherapy clinic. In 2021, the Cicatriza team came across the case of a patient with venous insufficiency, presenting an iatrogenic lesion characterized by the exposure of tendons, in the right lower limb (MID). Compressive therapy is considered the main alternative for the treatment of venous ulcers, however, not applied correctly, the harm outweighs the benefits, causing an ineffective treatment and increasing recurrence rates, the cost of treatment, the amount of exudate and consequently the risks of severe complications. Therefore, given the experience of the case, it is evident that the success in the treatment of venous ulcers is complex, dynamic and multifactorial. It is up to the nurse to manage the clinic, which involves the indication of therapies, appropriate products, professional evaluation and guidance, and therapeutic consent.